Covid-19: Good vs. Evil Dichotomy in News Media - Wardani, Agista; Adityo, Adityo (ARMADA : Jurnal Penelitian Multidisiplin, 2024)
Dichotomy may be expressed through the languages used on social media. When it comes to Covid-19, a pandemic that began in 2020, the global population is still unfamiliar with the problem and is in the process of adapting through various ideologies and strategies represented on social media. The objective of this research is to identify the dichotomy that surfaced during COVID-19 based on five reports from three YouTube channels. Qualitative discourse analysis was used by the researchers. This research focuses on the opinions of netizens on five reports that were posted on three YouTube channels about COVID-19 between January and May 2020, when Indonesia was enacting a "stay at home" policy. The findings show that comments from netizens fall into two categories. They are comments that support remaining at home to reduce the spread of Covid-19, as well as those that oppose staying at home for economic reasons. Furthermore, the remarks from one categorization overshadow the comments from the other classification. The remarks for each categorization see them as good and the other as wicked. Nonetheless, discourse analysis serves to reinvigorate social activity. As a result, mutual understanding is critical in dealing with this problem.